Arylene Diimide Phosphors: Aggregation Modulated Twin Room Temperature Phosphorescence from Pyromellitic Diimides. Issue 22 (19th April 2021) - Garain, Swadhin; Kuila, Suman; Garain, Bidhan Chandra; Kataria, Meenal; Borah, Aditya; Pati, Swapan K.; George, Subi J.
Abstract: Arylene diimide derived ambient organic phosphors are seldom reported despite their potential structural characteristics to facilitate the triplet harvesting. In this context, highly efficient room temperature phosphorescence (RTP) from simple, heavy‐atom substituted pyromellitic diimide derivatives in amorphous matrix and crystalline state is reported here. Multiple intermolecular halogen bonding interactions among these phosphors, such as halogen‐carbonyl and halogen‐π resulted in the modulation of phosphorescence, cyan emission from monomeric state and orange‐red emission from its aggregated state, to yield twin RTP emission. Remarkably, the air‐stable phosphorescence presented here own one of the highest quantum yield (≈48 %) among various organics in orange‐red emissive region. Abstract : Highly efficient room‐temperature phosphorescence, stable in air, from the simplest class of arylene diimides, i.e., pyromellitic diimides, is achieved. Aggregation modulated, colour tuneable phosphorescence emission from cyan to orange‐red in amorphous film and crystalline state is observed. The role of molecular design and weak intermolecular interactions in the observed properties is explained.